2016
DOI: 10.1007/s10753-016-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Power Laser (LPL) and Light-Emitting Diode (LED) on Inflammatory Response in Burn Wound Healing

Abstract: The aim of the study was to investigate the biochemical and molecular changes in the process of epidermal healing of burn injuries after therapeutic treatment with low-power laser (LPL) and light-emitting diode (LED). Rats were divided into six groups: skin without injury (Sham), burn wounds (BWs), BW + 660-nm LPL, BW + 904-nm LPL, BW + 632-nm LED, and BW + 850-nm LED. The burn wound model was performed using a 100 °C copper plate, with 10 s of contact in the skin. The irradiations started 24 h after the lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 61 publications
1
36
0
2
Order By: Relevance
“…2 Tissue damage in burn wound triggers a cascade of biochemical and molecular events that initiate a rapid but highly complex tissue repair process. 5 Recent study revealed the positive therapeutic effect of treating burn wounds with LED device and EGF solution 1,4 , but there is lack of study with synergistic effect of modalities mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Tissue damage in burn wound triggers a cascade of biochemical and molecular events that initiate a rapid but highly complex tissue repair process. 5 Recent study revealed the positive therapeutic effect of treating burn wounds with LED device and EGF solution 1,4 , but there is lack of study with synergistic effect of modalities mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…LED can reduce the inflammatory response by blocking the effects of ROS via activation of IL-6 and inhibition of cell proliferation and differentiation induced by growth factors via the MAPK pathway in burn wound model. 4 Application of EGF-containing formulations around lesions is widely used in wound treatments. Sen et al 1 reported applying EGF solution showed faster granulation, enhanced collagenization, patterned re-epithelialization and immunomodulatory effect in diabetic burn wound model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many studies have demonstrated that the hydrogen peroxide production by tissue-resident cells (i.e., synoviocytes), macrophages and neutrophils, could favor the sensitization of nociceptors via TRPA1 activation (Moilanen et al, 2015;Trevisan et al, 2016Trevisan et al, , 2014. Previous studies reported that thermal burn might increase the reactive species production, which could contribute to the tissue damage (Bhatia et al, 2016;Hoşnuter et al, 2004;Parihar et al, 2008;Silveira et al, 2016;Tanaka et al, 1999). In this sense, antioxidants are designed to reduce production and to capture reactive species that promote tissue lesion (Wasiak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are many effective therapeutic methods for diminishing inflammation, reducing swelling, relieving pain, improving microcirculation, and promoting wound healing, e.g., photodynamic, microcurrent, and ultrasonic treatments, among which the photodynamic therapy has been most widely used due to its noninvasive character and outstanding therapeutic effects. Specifically, the near infrared (NIR) light, used as a low‐level laser therapy (LLLT), has proven effective in controlling pain and reducing the healing time by stimulating collagen production, fibroblast proliferation, and the local microvasculature as well as by stimulating cellular metabolism to increase the potential for tissue regeneration . As a light source of NIR, the light emitting diodes (LEDs) have been recently used for medical treatments, showing great benefits to wound healing .…”
Section: Introductionmentioning
confidence: 99%